From propulsion to suction: Unraveling thrust reversal in propellers at intermediate Reynolds numbers - Rong Fu; Siyu Li; Yang Ding (Proceedings of the National Academy of Sciences, 2025)
This study investigates propeller hydrodynamics at intermediate Reynolds numbers ( Re ), crucial for small-scale robotic systems but still uncharted. Experiments on a propeller-driven underwater vehicle and numerical simulations reveal thrust reversal—a phenomenon where clockwise propeller rotation leads to backward motion—in the approximate range 1.3 ≲ Re ≲ 150 under specific conditions. Notably, counterclockwise rotation consistently results in backward motion. Simulations reveal that this behavior arises when centrifugal suction, an inward force along the axis caused by radial outward flow from the propeller’s rotation, dominates over fluid backward acceleration, the primary thrust mechanism at high Re . These findings provide critical insights into the unique dynamics of the intermediate Re regime and inform the design of efficient propulsion systems for miniature aquatic robots.